Diversity in the Corporate World: The Role of Law in Safeguarding Human Rights in the Workplace (Lembaga Contrarius Indonesia, 2026)
The essence of labor law is to protect workers from arbitrary employer actions. This employment relationship is interdependent, where business entities require workers for operations, while workers depend on wages. Therefore, the rights and responsibilities of both parties, the company and the workers, need to be kept in balance. One fundamental worker right is protection consistent with religious principles, humanity, Pancasila, and the State's goals, as enshrined in the 1945 Constitution of the Republic of Indonesia (UUD1945). This protection aims to guarantee workers' basic rights, equal opportunity, and the prevention of discrimination, in order to realize the welfare of workers and their families. However, business development and the interests of business actors must not be ignored. Legal instruments for upholding workers' rights include specific regulations, such as Law Number 13 of 2003 of the Republic of Indonesia concerning Manpower. This research employs a normative juridical method to examine the role of law in safeguarding human rights in the workplace.